2000
DOI: 10.1002/1097-4652(200010)185:1<36::aid-jcp3>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 and C/EBP transcription factors contribute tomda-7 gene promoter activity during human melanoma differentiation

Abstract: Treatment of human melanoma cells with a combination of recombinant fibroblast interferon (IFN-beta) and the protein kinase C (PKC) activator mezerein (MEZ) causes a rapid and irreversible suppression in growth and terminal cell differentiation. Temporal subtraction hybridization combined with random clone selection, reverse Northern hybridization, high throughput microchip cDNA array screening, and serial cDNA library arrays permit the identification and cloning of genes that are differentially expressed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Expression of the melanoma di erentiation associated gene-7 (mda-7) in actively proliferating normal melanocytes but not in melanoma cells has suggested that mda-7 may be a novel tumor suppressor gene (Jiang et al, 1995;Madireddi et al, 2000). Jiang et al (1996) demonstrated that mda-7 is a potent growth suppressor gene and selectively inhibits MDA-7-overexpressing cancer cells but not normal human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the melanoma di erentiation associated gene-7 (mda-7) in actively proliferating normal melanocytes but not in melanoma cells has suggested that mda-7 may be a novel tumor suppressor gene (Jiang et al, 1995;Madireddi et al, 2000). Jiang et al (1996) demonstrated that mda-7 is a potent growth suppressor gene and selectively inhibits MDA-7-overexpressing cancer cells but not normal human cells.…”
Section: Introductionmentioning
confidence: 99%
“…IL24 gene expression is dependent on transcription factors CEBPb, JUN, and FOS [ 55 , 56 ]. Transcription of all three was upregulated significantly by WX8 in A375 but not HFF1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitor Type Evidence in melanoma References c-Jun, Fos TAM67 c-Jun dominant negative derivative peptide Knocks down c-Jun in melanoma cell line from metastatic inguinal lymph node lesion Madireddi et al (2000) Blocked NFÎşB activation, downregulating genes for invasion and metastasis Matthews et al (2007) Reduced thymosin β4 in primary fibroblasts and melanoma cells Nummela et al (2006) Increased colony formation of primary and metastatic human melanoma cell lines in soft agar, induced vertical growth, loss of contact inhibition, morphology changes…”
Section: Targetmentioning
confidence: 99%